2022
DOI: 10.3389/fcvm.2022.911548
|View full text |Cite
|
Sign up to set email alerts
|

Distal Aortic Failure Following the Frozen Elephant Trunk Procedure for Aortic Dissection

Abstract: BackgroundAim of this study was to report and to identify risk factors for distal aortic failure following aortic arch replacement via the frozen elephant trunk (FET) procedure.MethodsOne hundred eighty-six consecutive patients underwent the FET procedure for acute and chronic aortic dissection. Our cohort was divided into patients with and without distal aortic failure. Distal aortic failure was defined as: (I) distal aortic reintervention, (II) aortic diameter dilatation to ≥ 6 cm or > 5 mm growth wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The mid- to long-term reports on incidence of aortic events after the FET vary in many studies ranging from approximately 16% to 47%. 5 , 21 , 22 , 23 , 24 This variability is mainly due to specifically selected patient cohorts under investigation and variable definitions of composite aortic events. Given the applicability of the FET procedure to many aortic pathologies, high incidence of distal aortic failure, and need for future aortic procedures, there is an urgent need for accurate predictors of aortic remodeling and adverse aortic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mid- to long-term reports on incidence of aortic events after the FET vary in many studies ranging from approximately 16% to 47%. 5 , 21 , 22 , 23 , 24 This variability is mainly due to specifically selected patient cohorts under investigation and variable definitions of composite aortic events. Given the applicability of the FET procedure to many aortic pathologies, high incidence of distal aortic failure, and need for future aortic procedures, there is an urgent need for accurate predictors of aortic remodeling and adverse aortic events.…”
Section: Discussionmentioning
confidence: 99%
“…Given the applicability of the FET procedure to many aortic pathologies, high incidence of distal aortic failure, and need for future aortic procedures, there is an urgent need for accurate predictors of aortic remodeling and adverse aortic events. 22 , 23 , 24 Furthermore, the FET procedure and its modified versions are increasingly more favored surgical approaches in the treatment of thoracic aortic disease in a younger patient population with tissue hereditary diseases, which translates to a lifetime of exposure and increased long-term risk of aortic events. Current surveillance techniques describe aortic remodeling after the FET in terms of TL and FL size parameters or aortic growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘spring back force’ is the force generated when the graft tries to straighten itself to its natural configuration, which acts upon the aortic wall, causing it to develop dSINE ( 30 ). On the contrary, Berger et al found that AAD is a significant risk factor for distal aortic failure after the FET procedure compared to CAD, likely due to vulnerability of the dissection membrane in the acute phase which increases the likelihood of developing dSINE ( 31 ). Furutachi et al noted that the Frozenix graft had a strong spring back force, whereas the THP design has been found to reduce the sheer stress on the intima which can explain its more favourable results in other studies ( 30 , 32 ).…”
Section: Dsinementioning
confidence: 98%
“…In a recent meta-analysis over 37 studies including 4178 patients, overall survival at 1, 3, and 5 years was 89.6%, 85.2%, and 82.0%, respectively, with freedom from reintervention of 93.9%, 89.3%, and 86.8%, respectively [11]. Thus, close follow-up in dedicated aortic centers is mandatory to decrease the risk of aortic-related events and to plan when needed a second-stage procedure [8][9][10][11][12][13]34,36].…”
Section: Long-term Outcomesmentioning
confidence: 99%